Assessment of Biological Risk Exposure Among Hospital Housekeepers at Wukari Teaching Hospital - Umaru, Isaac John; Asare, Solomon Ossom; Morgan, Akpan Usenobong; Umogbai, Debora Akinola; Olayemi, Abimbola Gbenga; Yeboah, Genevieve Akpah (African Journal of Biochemistry and Molecular Biology Research, 2025)
Hospital housekeepers play a vital role in maintaining hygiene and preventing infections within healthcare facilities, yet they are frequently exposed to biological hazards such as bloodborne pathogens, respiratory droplets, and contaminated waste, often without adequate protection or training. In Nigeria, particularly in tertiary institutions like Wukari Teaching Hospital, limited resources and weak enforcement of safety protocols further increase the vulnerability of non-clinical staff. This study aimed to assess the level of biological risk exposure among hospital housekeepers and identify gaps in personal protective equipment (PPE) usage, hygiene practices, and institutional support. A descriptive cross-sectional study was conducted among 60 hospital housekeepers at Wukari Teaching Hospital, with stratified random sampling ensuring representation across departments including wards, emergency, surgery, and outpatient units. Data were collected using structured questionnaires, direct observation checklists, and key informant interviews with infection control officers, and variables assessed included demographic data, exposure history, PPE usage, hygiene practices, and training experience. Quantitative data were analyzed using SPSS version 26, while qualitative responses were thematically coded. Findings revealed that 78.3% of housekeepers had direct contact with biological waste in the past six months, with blood, sputum, and vomit being the most common contaminants; only 41.7% consistently used full PPE, and just 36.7% reported that PPE was always available. Hand hygiene compliance was observed in 58.3% of cases, while 65% of respondents had never received formal infection control training, and only 30% felt adequately protected at work, with a majority suggesting improvements such as regular training, better supervision, and increased PPE supply. The study concludes that hospital housekeepers at Wukari Teaching Hospital face substantial biological risks due to frequent exposure, inconsistent PPE usage, and inadequate training, highlighting the urgent need for institutional reforms including structured infection control education, reliable PPE provision, and strict enforcement of hygiene protocols to protect this essential workforce and ensure a safe and resilient healthcare environment.